The formation of public housing policies in Brazil and Portugal - Milian, Eduardo (2021)
The decision to act or not to act in the face of a public problem is the central point that mobilizes governments, their resources and institutionality, to make public policy (Dye, 2011). The adoption of public policy by a government represents the set of priorities elected to pursue the collective interest. Public Choice Theory argues that public policies are sometimes captured by interest groups that alter their direction (Silvestre, 2010). The issue of housing has been understood in different ways, according to the dominant economic theory. Housing public policies, if considered from the perspective of social rights, represent a set of decisions and actions adopted by a government to promote social inclusion and the well-being of citizens (Maldonado, 2016). The objective of this research is to comparatively describe the evolution of public housing policy between Brazil and Portugal as an aspect of the political process. To do so, this paper analysed the context of the elaboration of the most forceful housing public policies: in 2009, the Minha Casa Minha Vida Program (PMCMV) in Brazil and, in 2018, the New Generation of Housing Policies (NGPH) in Portugal. The relevance of this comparison comes from the different stages in which these policies are: while in Brazil the PMCMV has been closed, in Portugal the NGPH is in the implementation phase. Thus, it is possible to observe development points for future actions. To organize the construction of the research, the methodology adopted considered the adoption of a plan with an interpretive paradigm, using the qualitative inductive method. The case study was used as an investigation strategy and the bibliographic and documental research was used as a research procedure. As results, it was observed that the Brazilian State oscillates in the prioritization of housing policies, depending on the current government strategies. Portugal for a long time considered that the responsibility for producing and providing housing belonged only to the individual (Agarez, 2020). In the case of Brazil, the PMCMV emerges as an anti-cyclical policy in the face of the economic crisis, while in the Portuguese case the strategic direction underpinning the NGPH is the emphasis on building requalification and territorial cohesion (Ferreira et al., 2019). In view of this, advances in access to the "home" element are recognized, even though contradictions and difficulties remain in the realization of the right to the city.